Is Magnus effect relevant for proppant settling in narrow fractures?. (September 2017) - Poła, Jakub; Bancewicz, Mateusz; Koza, Zbigniew
Abstract: Resolved Computational Fluid Dynamics-Discrete Element Method is an attractive approach for simulating multiphase flows of fluid-solid mixtures, as it includes a 4-way coupling. However, many of its modernimplementations neglect the torque coupling between the fractions. Here we augment the CFDEM®coupling toolkit to allow it to capture this interaction and use it to simulate sedimentation of spherical grains in two-dimensional narrow fractures, with and without grain rotation taken into account. While the rotational effects turns out to change the dynamics of individual grains, it does not affect the average settling velocity significantly.